2015
DOI: 10.1002/2014jc010312
|View full text |Cite
|
Sign up to set email alerts
|

Nodal variations and long‐term changes in the main tides on the coasts of China

Abstract: The long-term changes in the main tidal constituents (O 1 , K 1 , M 2 , N 2 , and S 2 ) along the coasts of China and in adjacent seas are investigated based on 17 tide-gauge records covering the period 1954-2012. The observed 18.61 year nodal modulations of the diurnal constituents O 1 and K 1 are in agreement with the equilibrium tidal theory, except in the South China Sea. The observed modulations of the M 2 and N 2 amplitudes are smaller than theoretically predicted at the northern stations and larger at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 61 publications
11
73
1
1
Order By: Relevance
“…The effects of 18.61 years of the lunar nodal cycle on the SLA estimation have been investigated in the past for its considerable amplitude in the study area [8,[48][49][50][51] 18.61 in Equation (1), and a A 2`B2 denotes the amplitude of the lunar nodal cycle). Table 2 lists the SLA calculated from least squares fitting (Equation ( Note that in long records, the lunar cycle has little influence on the calculated acceleration, but in shorter records the results can be strongly affected by this cycle if it is not removed, as demonstrated in Table 2.…”
Section: Effects Of Lunar Nodal Cycle On Sea Level Acceleration Estimmentioning
confidence: 99%
“…The effects of 18.61 years of the lunar nodal cycle on the SLA estimation have been investigated in the past for its considerable amplitude in the study area [8,[48][49][50][51] 18.61 in Equation (1), and a A 2`B2 denotes the amplitude of the lunar nodal cycle). Table 2 lists the SLA calculated from least squares fitting (Equation ( Note that in long records, the lunar cycle has little influence on the calculated acceleration, but in shorter records the results can be strongly affected by this cycle if it is not removed, as demonstrated in Table 2.…”
Section: Effects Of Lunar Nodal Cycle On Sea Level Acceleration Estimmentioning
confidence: 99%
“…Only over the past 20 years (since the digitization, concatenation, and public dissemination of regional and global databases of tide gauge records; Woodworth et al, ) has it been determined that significant and widespread positive and negative trends in tidal levels (and tidal currents) are occurring at many locations around the world (e.g., Devlin et al, ; Feng et al, ; Flick et al, ; Jay, ; Müller et al, ; Ray, ; Talke et al, ; Talke & Jay, ; Woodworth, ). Remarkably, the rates of tidal level changes observed are of similar magnitudes to the rate of mean sea level (MSL) rise at some sites; for example, Mawdsley et al () found increases in tidal range at Astoria (USA), Wilmington (USA), Delfzijl (the Netherlands), Cuxhaven (Germany), and Calais (France) of >25 cm over the last century.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that tides are evolving at diverse rates worldwide without any apparent relationship to astronomical forcing (Haigh et al, ; Mawdsley et al, ; Müller et al, ; Woodworth, ). On a regional scale, changes in major diurnal and semidiurnal tides have been observed in the Eastern Pacific (Jay, ), in the Gulf of Maine, (Ray, ), in the North Atlantic (Müller, ; Ray, ), in China (Feng et al, ; Feng & Tsimplis, ), in Japan (Rasheed & Chua, ), and at Pacific islands, though a reduction in gauge timing errors over time can cause spurious increases in amplitude (Zaron & Jay, ).…”
Section: Introductionmentioning
confidence: 99%